2002
DOI: 10.3892/ijmm.9.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Effects of red wine and wine polyphenol resveratrol on platelet aggregation in vivo and in vitro

Abstract: Low to moderate consumption of red wine reportedly has a relatively greater benefit than other alcoholic beverages in the prevention of atherosclerosis and coronary heart disease (CHD). This beneficial effect is increasingly attributed to the polyphenol resveratrol, present in red wine. In the present study, we investigated the effects of resveratrol and red wine on aggregation of platelets isolated from healthy, normotensive male volunteers and in rabbits with experimental hypercholesterolemia. Platelet aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
161
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(165 citation statements)
references
References 12 publications
4
161
0
Order By: Relevance
“…In addition, recent studies show that resveratrol sustains healthy nerves and important brain functions including cognitive processes [43]- [46].…”
Section: Polyphenols In Healthmentioning
confidence: 99%
“…In addition, recent studies show that resveratrol sustains healthy nerves and important brain functions including cognitive processes [43]- [46].…”
Section: Polyphenols In Healthmentioning
confidence: 99%
“…However, RS has been shown to inhibit the aggregation of platelets (Bertelli et al, 1996b;Bhat et al, 2001;Fan et al, 2008). Suppression of platelet aggregation by RS in rabbits supplemented with hypercholesterolemic diet and reduced atherosclerosis in genetic hypercholesterolemic mice were also demonstrated (Zini et al, 1999;Wang et al, 2002b). However, RS failed to demonstrate such effects in whole blood as the mechanism might be through inhibition of mitogen-activated protein kinases in platelets (Kirk et al, 2000).…”
Section: Suppression Of Platelet Aggregation By Rsmentioning
confidence: 99%
“…However, various other studies have failed to show a change in lipids and lipoprotein profile after treatment with RS in vivo (Wilson et al, 1996;Soleas et al, 1997;Turrens et al, 1997Turrens et al, , 1999Fremont, 2000;Wang et al, 2002b). Table 1 shows a list of studies analysing the effects of RS on lipid and lipoprotein levels in various experimental conditions.…”
Section: Effect Of Rs On Lipids and Lipoprotein Levelsmentioning
confidence: 99%
“…Studies in animals and humans have suggested that RW and RW polyphenols may improve lipid profiles, reduce platelet aggregation, reduce endothelial dysfunction and improve blood pressure; however, their effect on arterial stiffness remains to be further investigated (Goldberg et al, 1996;Diebolt et al, 2001;Wang et al, 2002;Ralay Ranaivo et al, 2004). To date, one study has investigated the effects of RW polyphenols (7alcohol) on arterial stiffness (Mahmud and Feely, 2002).…”
Section: Introductionmentioning
confidence: 99%